From Chalkboards to Steam Engines: Early Adoption of Compulsory Schooling, Innovation, and Industrialization - Francesco Cinnirella; Elona Harka (CESifo GmbH, 2025)
Empirical evidence on the historical role of Compulsory Schooling Laws (CSL) for the spread of mass education is mixed at best. This is also due to the difficulty of identifying exogenous variation in the application of CSL. We exploit an almost unique feature of a CSL in 1877 Italy which was gradually implemented across municipalities based on the teacher to population ratio. This criterion generates a sharp discontinuity which can be exploited to estimate the causal effect of the early implementation of CSL on economic outcomes. Estimates based on a regression discontinuity design show that CSL had a positive long-term effect on innovation and industrial employment. Consistent with the main objective of the reform, CSL had a positive effect on human capital by increasing enrollment rates in technical schools and, more in general, the literacy rate. The results are robust to a series of placebo, falsification and manipulation tests. This study provides important policy implications in favor of the early implementation of CSL to increase the average level of education which, in turns, brings about positive effects on innovation and industrialization.
Keywords: N33; O14; O43; I25; 330; education; industrialization; literacy; patents; liberal Italy